2011
DOI: 10.1242/jcs.087403
|View full text |Cite
|
Sign up to set email alerts
|

FAT10 mediates the effect of TNF-α in inducing chromosomal instability

Abstract: SummaryTumor necrosis factor-alpha (TNF-a) plays important roles in chronic inflammation-associated tumorigenesis but the mechanisms involved remain poorly understood. Previously, we reported that high levels of FAT10 led to chromosomal instability that is mediated by an abbreviated mitotic phase. Here, we show that TNF-a induces FAT10 gene expression through TNF receptor 1 (TNFR1) and activates the NF-kB pathway in HCT116 and SW620 cells. TNF-a treatment also leads to an abbreviated mitotic phase that can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
70
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 83 publications
6
70
1
Order By: Relevance
“…Tumor formation by TNF-␣-induced and thus FAT10 expressing HCT116 cells in nude mice was diminished when the mice were treated at the same time with silibinin which correlated with reduced FAT10 expression in the tumors. The dependency of endogenous FAT10 expression on NF-B signaling was further supported by data showing that the induction of FAT10 expression by TNF-␣ was greatly diminished when p65 was downregulated by specific siRNAs in HCT116 and HepG2 cells (Gao et al, 2015;Ren et al, 2011).…”
Section: What Are the Mechanisms Behind Fat10 Overexpression?mentioning
confidence: 78%
See 4 more Smart Citations
“…Tumor formation by TNF-␣-induced and thus FAT10 expressing HCT116 cells in nude mice was diminished when the mice were treated at the same time with silibinin which correlated with reduced FAT10 expression in the tumors. The dependency of endogenous FAT10 expression on NF-B signaling was further supported by data showing that the induction of FAT10 expression by TNF-␣ was greatly diminished when p65 was downregulated by specific siRNAs in HCT116 and HepG2 cells (Gao et al, 2015;Ren et al, 2011).…”
Section: What Are the Mechanisms Behind Fat10 Overexpression?mentioning
confidence: 78%
“…As already pointed out, FAT10 mRNA and protein expression is highly and synergistically inducible in all cell types by the pro-inflammatory cytokines IFN-␥ and TNF-␣ (Aichem et al, 2010;Raasi et al, 1999;Ren et al, 2011) or by a combination of TNF-␣ and IL-6 as shown in HepG2 cells (Choi et al, 2014). In HCT116 cells it was shown, that TNF-␣ signaling via the TNF-␣ receptor 1 (TNFR1) induced FAT10 expression, a receptor mainly found on tumor and stromal cells where it mediates the activation of NF-B (Balkwill, 2009;Ren et al, 2011). The analysis of the FAT10 promoter sequence revealed seven potential p65/NF-B binding sites as well as three binding sites for transcription factors of the family of signal transducer and activator of transcription (STAT)3 (Canaan et al, 2006;Choi et al, 2014;Gao et al, 2015).…”
Section: What Are the Mechanisms Behind Fat10 Overexpression?mentioning
confidence: 81%
See 3 more Smart Citations